Tinjauan Yuridis Terhadap Konflik Pemerintah Daerah Dan Pihak Pengelola Dalam Kasus Mega Mall Bengkulu - Predi Alexander Sitorus; Arki Sandra; Abduh Falah Ridho; Pandji Ramadhan; Aditya Gite (GLOBAL SCIENTS PUBLISHER, 2026)
This research aims to conduct an in-depth juridical review of the conflict between the Regional Government of Bengkulu City and the management party in the dispute over the utilization of regional assets at Mega Mall Bengkulu, where the essence of the problem stems from the lack of synchronization between the implementation of the Build-Operate-Transfer (BOT) agreement and current regulations regarding the Management of Regional Property. Utilizing a normative legal research method that emphasizes a statutory and case-based approach, the legal arguments in this study construct that the dispute arose due to substantial weaknesses in old contractual clauses that failed to accommodate the principle of asset value escalation, thereby creating a disparity between the fixed contributions received by the regional government and current market appraisal values, which ultimately leads to potential losses in regional finances. Furthermore, this analysis demonstrates that the position of the Bengkulu City Government in this legal relationship is not merely private as a contractual partner, but also carries a public obligation under Government Regulation No. 28 of 2020 to optimize state assets; thus, the act of renegotiation or contract termination against a management party deemed to be in breach of contract (wanprestatie) regarding Regional Original Revenue (PAD) obligations is legally valid, provided it is conducted through proper legal procedures. This study concludes that the resolution of such conflict requires a redefinition of the contractual relationship through a contract addendum that prioritizes the principles of distributive justice and legal certainty, in order to guarantee investment continuity while simultaneously protecting the regional economic rights that have been neglected due to unaccountable asset management.